2013
DOI: 10.15623/ijret.2013.0211042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Tribological Characteristics of Aa2024+10% Fly Ash Composite in Non-Heat Treated and Heat Treated Conditions

Abstract: There has been search for the low cost and low density reinforcements for reducing the cost of composites. One prospective reinforcement in this regard is the fly ash, which is abundantly available as a waste product from thermal power plants. Because of unique nature of physical and chemical properties of the fly ash it is tried as reinforcement by many researchers in the recent past. In the present investigation composite used contains fly ash particles [10% by wt] reinforced with wrought aluminium alloy AA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Alidokht et al [9] reported a slight increase in the wear loss 25% for increasing load from 10 to 25 N and 30% for increasing load from 25 N to 40 N for Al + SiC composites. Other authors [12][13][14][15] have also reported the influencing of increasing loads on the wear behavior of similar composites (see Table 1), however, the results might not agree with the current experiment. The reason behind that is the difference in the wear setup mechanism (such as reduction of vibration at increasing loads) peculiar to the current wear evaluation setup this project uses.…”
Section: Results (Bulgular)contrasting
confidence: 80%
“…Alidokht et al [9] reported a slight increase in the wear loss 25% for increasing load from 10 to 25 N and 30% for increasing load from 25 N to 40 N for Al + SiC composites. Other authors [12][13][14][15] have also reported the influencing of increasing loads on the wear behavior of similar composites (see Table 1), however, the results might not agree with the current experiment. The reason behind that is the difference in the wear setup mechanism (such as reduction of vibration at increasing loads) peculiar to the current wear evaluation setup this project uses.…”
Section: Results (Bulgular)contrasting
confidence: 80%